Building Digital Literacy Through Technology Adoption: Evidence from MSMEs in the Digital Era - Candra Surya; Ganefri Ganefri; Asmar Yulastri; Yuliana Yuliana (AL-ISHLAH: Jurnal Pendidikan, 2026)
In the digital era, information technology adoption has become a strategic factor in improving the performance of Micro, Small, and Medium Enterprises (MSMEs). Nevertheless, many MSMEs fail to fully benefit from digital technologies due to limited digital literacy, reflecting an education-related gap between technology utilization and human capacity development. This study aims to analyze the effect of information technology adoption on MSME performance, with digital literacy serving as a mediating variable that represents learning and skill development processes. A quantitative research design was employed using a survey of 330 MSME owners and managers across various business sectors. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Instrument validity and reliability were established through convergent validity, discriminant validity, and composite reliability tests. The results indicate that information technology adoption has a positive and significant effect on digital literacy and MSME performance (β 0). Furthermore, digital literacy partially mediates the relationship between technology adoption and performance, while the model demonstrates moderate explanatory power as indicated by R² values. This study contributes to education scholarship by positioning digital literacy as a mediating learning construct in MSME performance research. Practically, the findings highlight the importance of designing targeted digital training, literacy programs, and curriculum development for MSME capacity building to support sustainable economic growth.